A study on cardiotocography for predicting fetal prognosis in high-risk pregnancy - Kanwat, Babita; Singhal, Megha; Chauhan , Madhubala; Chaubisa , Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The admission cardiotocography (CTG) in high-risk obstetrics patients for continuous monitoring of fetal heart rate (FHR) has become crucial in the modern obstetric practice. It is not only a good screening and inexpensive test but also non-invasive, easily performed and interpreted. Methods: This was a prospective observational study conducted in department of obstetrics and gynaecology, Pannadhay Rajkiya Mahila Chikitsalaya at RNT medical college, Udaipur from April 2022 to September 2022. A total of 100 high risk obstetrics patients were subjected to cardiotocography (CTG). The Women eligible for the study were those who had gestational age ≥32 weeks with cephalic presentation in first stage of labour with singleton fetus in vertex presentation and categorised as high-risk during the time of admission. Results: A total of 100 high risk obstetric patients were subjected to CTG. Out of these common high-risk factors in our study consisted of postdated pregnancy (21%) followed by pre-eclampsia (19%), oligohydramnios (16%) cord around neck (13%). Majority of them (47%) fall under 20-25 years and constituted by primigravida (59%). CTG was reactive in (65%), non-reactive in 25% of cases and 10% patients had suspicious tracings. The incidence of neonatal intensive care unit (NICU) admission, fetal distress and APGAR score less than 7 was significantly higher with suspicious and nonreactive CTG than reactive CTG. Conclusions: CTG test is a simple, non-invasive screening test should be used in high risk pregnancy as admission test. The heavy load of constant monitoring and adverse perinatal outcome can be reduced by CTG monitoring in high-risk obstetrics patients.